Abnormal activity of transcription factors gli in high-grade gliomas - Volnitskiy, Andrey; Shtam, Tatiana; Burdakov, Vladimir; Kovalev, Roman; Konev, Alexander; Filatov, Michael (PLOS ONE, 2019)
Malignant transformation is associated with loss of cell differentiation, anaplasia. Transcription factors gli, required for embryonic development, may be involved in this process. We studied the activity of transcription factors gli in high-grade gliomas and their role in maintenance of stem cell state and glioma cell survival. 20 glioma cell lines and a sample of a normal adult brain tissue were used in the present study. We found the expression of gli target genes, including GLI1 and FOXM1, in all tested glioma cell lines, but not in the normal tissue. Interestingly, the expression of gli target genes in some glioma cell lines was observed together with a high level of their transcriptional repressor, Gli3R. Knockdown of GLI3 in one of these lines resulted in decrease of gli target gene expression. These data suggest that Gli3R does not prevent the gli target genes transcription, and gli3 acts in glioma cells more as an activator, than a repressor of transcription. We observed that gli regulated the expression of such genes, as SOX2 or OCT4 that maintain stem cell state, and TET1, involving in DNA demethylation. Treatment with GANT61 or siRNA against GLI1, GLI2, or GLI3 could result in complete glioma cell death, while cyclopamine had a weaker and line-specific effect on glioma cell survival. Thus, the gli transcription factors are abnormally active in high-grade gliomas, regulate expression of genes, maintaining the stem cell state, and contribute to glioma cell survival.